2017
DOI: 10.17665/1676-4285.20175623
|View full text |Cite
|
Sign up to set email alerts
|

Absenteísmo, rotatividade e indicadores de qualidade do cuidado em enfermagem: estudo transversal

Abstract: Aim: to analyze the indexes of absenteeism and turnover, and their relationship with quality indicators in assistance. Method: this is a transversal study, performed with records of absences/changes of 59 nursing professionals of an intensive care unit; records of quality/incidence indicators, and medical records of the 108 patients hospitalized during the period of data collection. The coefficient of linear correlation was used among the indicators of assisting management and quality control. Results: the ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
3
0
2
Order By: Relevance
“…However, in the same study, she found that women were more likely to be absent than men (4.4%), at a rate of 19.9%, due to caring for a family member. de Arruda Leitão et al [21] also found that, in terms of absenteeism, there are more employees with lower education than those with higher education. The absenteeism rate is a disruptive factor in the organization of work and has a negative impact on the patients themselves and on the other employees, who are overworked and consequently more likely to fall ill or even be injured.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, in the same study, she found that women were more likely to be absent than men (4.4%), at a rate of 19.9%, due to caring for a family member. de Arruda Leitão et al [21] also found that, in terms of absenteeism, there are more employees with lower education than those with higher education. The absenteeism rate is a disruptive factor in the organization of work and has a negative impact on the patients themselves and on the other employees, who are overworked and consequently more likely to fall ill or even be injured.…”
Section: Discussionmentioning
confidence: 95%
“…He also found that there is no direct correlation between the working conditions and safety and health of the respondents and the number of days of sickness absence. de Arruda Leitão et al [21] found that most of the causes are related to injuries or diseases of the musculoskeletal system, due to direct work with patients (lifting, changing positions in bed, moving, etc.). Mastnak [32] found in his study that the satisfaction of nursing staff with regard to working conditions, safety, and health at the workplace, does not statistically prove the causes of absenteeism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Todas essas características ocorrem sem que haja o "amor à instituição", um elemento simbólico da cultura organizacional (VENTURA; VELLOSO; ALVES, 2020). Assim, o desafio dos gestores em saúde não é somente manter seus colaboradores "apaixonados" pelo seu fazer, mas também "apaixoná-los" pela instituição, já que, uma alta rotatividade de pessoal leva a uma predisposição de pacientes a riscos, impactando diretamente na qualidade da assistência prestada (LEITÃO et al, 2017).…”
Section: Análise E Discussão Dos Resultadosunclassified
“…Participaram do estudo os hospitais públicos e privados de grande porte (número de leitos maior do que 150) localizados na região metropolitana de Salvador (BA), selecionados por meio dos dados da Secretaria da Saúde do Estado da Bahia, com identificação de 20 hospitais. Optou-se por estudar esses hospitais por assistirem um grande número de pacientes nas mais diversas especialidades, resultando num maior nível de complexidade assistencial, bem como pela alta rotatividade de pacientes e profissionais [13][14][15] , o que pode implicar aumento da possibilidade da ocorrência de EA nos pacientes internados nessas instituições.…”
Section: Métodounclassified